2000
DOI: 10.1038/sj.leu.2401730
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects induced by variable levels of BCR-ABL protein in the pluripotent hematopoietic cell line UT-7

Abstract: There is currently no satisfactory model allowing analysis of dose-effect relationships of BCR-ABL proteins in human hematopoietic cells. To study comparatively the proliferative, differentiative and anti-apoptotic actions of different levels of BCR-ABL proteins in the context of the same cellular background, we have introduced the BCR-ABL gene into the GM-CSF-dependent pluripotent human cell line UT-7. Individual clones expressing BCR-ABL were analyzed by Western blots. After normalization to equivalent level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…Low disease incidence and long latency in our model are likely to result from lower expression of the p210 BCR/ABL transgene when compared with models using the robust but nonspecific retroviral and metallothionein promoters. Although an increase in the dosage of p210 BCR/ABL has been shown to be crucial for both antiapoptotic effects (28,29) and resistance of the disease to treatment (30), perhaps the expression levels found in our transgenic mice more closely mimic those found in preleukemic and chronic phase patients (10,31,32). The strain-specific decrease in CML-like disease also suggests that heritable factors, in particular genetic backgrounds, can either enhance or suppress the physiologic effects of BCR͞ABL.…”
Section: Discussionmentioning
confidence: 61%
“…Low disease incidence and long latency in our model are likely to result from lower expression of the p210 BCR/ABL transgene when compared with models using the robust but nonspecific retroviral and metallothionein promoters. Although an increase in the dosage of p210 BCR/ABL has been shown to be crucial for both antiapoptotic effects (28,29) and resistance of the disease to treatment (30), perhaps the expression levels found in our transgenic mice more closely mimic those found in preleukemic and chronic phase patients (10,31,32). The strain-specific decrease in CML-like disease also suggests that heritable factors, in particular genetic backgrounds, can either enhance or suppress the physiologic effects of BCR͞ABL.…”
Section: Discussionmentioning
confidence: 61%
“…High levels of Bcr-Abl were required to protect the cell lines from apoptotic stimuli. In contrast, Issaad et al (2000) have shown that low-level expression of Bcr-Abl in the pluripotent human cell line, UT-7, was insufficient to produce a growth factor independent phenotype. Only when cells expressed high levels of Bcr-Abl did they become independent of the need for growth factors.…”
Section: Introductionmentioning
confidence: 93%
“…Drug resistance depends also on the high expression levels of BCR/ABL suggesting amplification/hyperactivation of signaling pathways and/or DNA repair mechanisms relevant for response to genotoxic stress (Cambier et al, 1998;Issaad et al, 2000;Keeshan et al, 2001). Since drug resistance depended on the BCR/ABL kinase activity, it was most likely not owing to clonal evolution arising from the accumulation of additional genomic aberrations.…”
Section: Consequences Of Ftks Expressionmentioning
confidence: 99%